Solid phase extraction and preconcentration of nickel in water samples with activated carbon-PAR and flame atomic absorption spectrometry - Kaya, Gokce; Akdeniz, Ismail; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2008)
Preconcentration is commonly used if the concentration of trace elements in the sample is lower than the detection limit of the analytical technique. Furthermore, a number of interfering constituents can be removed by using preconcentration procedures. In this study, a simple, sensitive, accurate and selective method was optimized for determination of ultratrace levels of nickel. For this purpose, Ni was complexed with PAR and adsorbed on the activated carbon. It was found that reproducible recoveries LIP to 90% were achieved at the pH range of 4.0-7.0 with a contact time of 30 minutes. The adsorbed nickel was eluted by adding concentrated nitric acid and measured by flame atomic absorption spectrometry (FAAS). The optimized enrichment method was applied to the determination of nickel in natural water samples. The detection limit was found to be 0.6 ng mL(-1). The relative standard deviation (RSD) was found to be 9% by using 300 mL of 10 ng mL(-1)Ni, for 10 replicate enrichment procedures. Nickel concentrations in the studied water samples were found to be in the ranges of 3.0-57 ng mL(-1).
Keywords: Trace-Metal Ions; Amberlite Xad-2; Natural-Water; Spectrophotometric Determination; Simultaneous Enrichment; Aas Determination; Cadmium; Cobalt; Lead; Copper